Fate of triclosan, triclocarban, and their transformation products in wastewater under nitrifying conditions. (April 2019) - Armstrong, Dana L.; Lozano, Nuria; Rice, Clifford P.; Ramirez, Mark; Torrents, Alba
Highlights: Nitrification wastewater treatment was simulated using laboratory bioreactors. Greater triclosan reduction occurred at a pH range of 8.5–9.5. Methyltriclosan was formed under both treatment conditions. Triclocarban and 2, 4-dichlorophenol levels did not change during treatment. Abstract: The nitrification process was simulated using benchtop bioreactors to gain insight into the fate of the antimicrobials triclosan (TCS) and triclocarban (TCC), as well their transformation products, during wastewater treatment. Currently, little information exists on the impact of nitrification treatment on concentrations of TCC, TCC degradation products, and TCS degradation products. Reactors were run using samples collected from a large municipal wastewater treatment plant at two pH ranges (6.5–7.5 and 8.5–9.5) for 171 h to simulate an extended hydraulic retention time (HRT). TCS was degraded under both pH conditions, with a 28.5% overall reduction in solids samples when the pH range was 6.5–7.5 and an overall reduction of 83.2% in solids samples when the pH ranged 8.5–9.5. Methyltriclosan (MeTCS) was formed in solids samples during both treatment conditions. MeTCS formed the most rapidly during the first 25 h of treatment at pH 8.5–9.5. Levels of 2, 4-dichlorophenol, a TCS photolysis product, and TCC did not change over the 171 h treatment period, indicating that nitrification is not an effective treatment for reduction of these compounds. Three TCC dechlorination products and triclosan-O-sulfate were not observed at or above the limit of quantitation in any bioreactor samples.